2021
DOI: 10.1111/jfd.13484
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish intestinal transcriptome highlights subdued inflammatory responses to dietary soya bean and efficacy of yeast β‐glucan

Abstract: The intestinal epithelium acts as a selective barrier, and the epithelial cells evoke appropriate responses to microbial signals and antigenic factors (Soderholm & Pedicord, 2019). Normal functioning of the associated mucosal barrier, which includes the epithelial layer and lamina propria, is vital to carry out digestion and nutrient absorption by the intestine (Farré et al., 2020). A compromised mucosal barrier increases the permeability of the intestine, and such a condition allows undesirable luminal antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 126 publications
(178 reference statements)
3
8
0
Order By: Relevance
“…The software ImageJ ( 46 ) was used for quantifying the histological indices. The histological indices that were evaluated were: length of the villi, width of lamina propria, submucosa thickness and tunica muscularis thickness, as described in our previous publication ( 47 ) ( Supplementary Figure 1 ). Liver vacuolation was assessed by evaluating two parameters-average lipid vacuole area and average lipid vacuole number in a selected area of the liver ( Supplementary Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The software ImageJ ( 46 ) was used for quantifying the histological indices. The histological indices that were evaluated were: length of the villi, width of lamina propria, submucosa thickness and tunica muscularis thickness, as described in our previous publication ( 47 ) ( Supplementary Figure 1 ). Liver vacuolation was assessed by evaluating two parameters-average lipid vacuole area and average lipid vacuole number in a selected area of the liver ( Supplementary Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous genomic studies conducted at the tissue level identified several GOs commonly altered in the liver and/or intestine when fish species were fed with high SBM content and/or high FM replacement with plant protein sources, including lipid (fatty acid) metabolism, ion transport, bile acid biosynthesis and secretion, steroid biosynthesis, cell proliferation and apoptosis, oxidative stress, digestion and absorption of nutrients (proteins, lipid, vitamins, and minerals), purine metabolism, and immune system response [13][14][15]23,73,93,94]. Although tissue mRNA expression was not explored here, bioinformatic prediction of potential mRNAs targets of DE miRs can help to understand how DE miRs might impact particular physiological processes [18] and-in the present case-to provide new insights on the limiting factors of high SBM inclusion in aquafeeds.…”
Section: Circulating Non-coding Rnasmentioning
confidence: 99%
“…Transport (GO:0006810) was in agreement with the altered transport reported at transcriptional level in previous genomic studies in fish fed with diets including a high SBM content and/or where FM and FO were totally replaced with plant sources. Several studies reported the altered expression of genes from different solute carrier families (e.g., slc26a6l and slc6a19 downregulation), ATP-binding cassette (e.g., abca1 upregulation), and sodium-associated and/or choline transporter genes [21,73,94]. Likewise, members of the solute carrier family 22, choline transporter-like protein 4, choline O-acetyltransferase, or ATP-binding cassette transporter A1 (abca1), among others, were predicted to be targets of the identified DE miRs.…”
Section: Circulating Non-coding Rnasmentioning
confidence: 99%
“…In turn, the affected gut, as well as gut microbes, stimulate immune response and metabolic activity, which leads to chronic inflammation and eventually evolves into a chronic disease, so regulating gut flora is one of the ways to suppress inflammation ( Chen et al, 2021 ). Rehman et al found that feeding zebrafish with Fermentum β-polysaccharide altered the diversity and composition of the zebrafish gut microbiota significantly reduced the width of the intrinsic layer of the zebrafish gut, and led to a reduction in inflammation in zebrafish ( Rehman et al, 2021 ). Relevant studies have proved that long-term oral administration of Fermentum β-polysaccharide is beneficial to increasing beneficial flora, reducing harmful flora (such as enterohemorrhagic Escherichia coli), increasing the production of short-chain fatty acids (SCFA), and preventing colitis ( Gudi et al, 2020 ).…”
Section: Activitymentioning
confidence: 99%